Vocationalisation of Secondary Education Revisited - Maclean, Rupert; Wilson, David N.; Lauglo, Jon.; Maclean, Rupert; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The book is a cutting-edge contribution to the debate which has occurred for some time on the pros and cons of secondary education becoming more closely and explicitly related to preparing young people for the world of work. The book provides concrete examples of the vocationalisation of secondary education, with particular reference to the situation in Africa. The target audience for the book includes policy-makers, practitioners, administrators, education planners, researchers, teachers and teacher educators with a concern about the relationship between secondary education and education for the world of work (with particular reference to technical and vocational education and training - TVET.) The book appears in the Springer book series on 'Technical and Vocational Education and Training: Issues, Concerns and Prospects' and compliments the 'International Handbook of Technical and Vocational Education and Training' and other publications in the' International Library of TVET' all of which are publications of the 'UNESCO-UNEVOC International Centre for TVET' in Bonn, Germany
Perspectives and Overviews -- Vocationalised Secondary Education Revisited -- Setting the Context: An Overview of Secondary Education Reform with Particular Reference to the Asia-Pacific Region -- Promise and Performance in Vocationalised Secondary Education: Has the Baby Been Thrown Out with the Bath Water? -- Country Case Studies -- Pre-vocational Secondary Education in Botswana -- Vocationalisation of Secondary Education in Ghana -- Vocationalisation of Secondary Education: Kenya Case Study -- Labour Market Impact -- Technical and Vocational Education and Training in Mozambique: Better than Its Reputation -- Economic Returns to Vocational Courses in U.S. High Schools.
Keywords: EDUCATION; EDUCATION AND STATE; EDUCATION; PROFESSIONAL & VOCATIONAL EDUCATION; EDUCATION (GENERAL).; LEADERSHIP & ADMINISTRATION; EDUCATIONAL POLICY